PENGELOLAAN BAHAN ORGANIK DENGAN SISTEM TANPA OLAH TANAH DAN KOMPOS LANSUNG DITEMPAT - Yulinar Zubaidah; Ridwan Ridwan (Jurnal Solum, 2006)
The addition of the organic matter into a soil will improve the physical, chemical and biological properties of the soil and the soil quality can be maintained. The organic matter application into agriculture field can be done directly at no tillage system farming or can be composted insitu. In the no tillage system weeds were controlled by herbicide. Application and insitu composting of the crop residual and weed were incorporated into the soil before maize planting. The results of the experiment showed that, the direct (insitu) composting system gave the higher yield of maize and more profitable than without application of organic matter. The utilization of organic matter in no tillage system and insitu composting were more advantageous because the organic matter were not processed such as compost, and cost as well as time was more efficient. Keywords: No tillage system, insitu composting, maize, palm trees